Ischemic heart disease and reflux-esophagitis: complexities of the differential diagnosis and treatment. - Yu. N. Belenkov; Ye. V. Privalova; A. O. Yusupova; M. V. Kozhevnikova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To illuminate state-of-the-art of issue of ischemic heart disease and reflux-esophagitis combination and options of treatment of comorbide patients.Original positions. Ischemic heart disease (IHD) and reflux-esophagitis (RE) are one of the most frequent diseases of cardio-vascular and alimentary systems. Common risk factors play important role in high prevalence of comorbide course of IHD and RE. Close anatomic position and common innervation of the heart and the esophagus trigger effect of gastroesophageal reflux on coronary vasoconstriction and disorders of heart rhythm at patients with IHD. Present studies show treatment effect, aimed on RE, at patients with IHD: decrease in number of myocardial ischemia and arrhythmia attacks. Application of prokinetics in complex treatment of RE at IHD patients is pathogenically proven. Combination of diseases requires long treatment, dictates necessity of choice of the safe agent, having no negative effect on the course of IHD.Conclusion. Mutual effect on development and progression of symptoms of cardio-vascular and alimentary diseases causes not only certain diagnostic difficulties, but also necessitates search for improvement of diagnostic and treatment methods in comorbide patients with IHD and RE.